FACTORS INFLUENCING ENTREPRENEURIAL INTENTIONS OF STUDENTS SPECIALIZING IN THE TOURISM INDUSTRY - Francisco Dias; Antonina N. Tret'yakova; Tamer Atef; Joanna Kosmaczewska; Regina Navickiene (Высшее образование в России)
The article describes the results of an international study of entrepreneurial intentions of students specializing in tourism and hospitality. As a result of the agreed questionnaire and further processing of the data the factors influencing entrepreneurial intentions were revealed. For students from Russia, Portugal, Poland, Lithuania and Oman the tendency to create new business isn't statistically significantly different. Men are more likely to become entrepreneurs than women. For students inclination towards entrepreneurship is motivated primarily by the attractiveness of this activity. Negative factors are not significant, students do not evaluate them as a barrier to starting a business. On the tendency to create new business positively affect entrepreneurial values of significant groups, the belief in the ability to provide their personal (psychological) and social security, as well as entrepreneurship education.